2013
DOI: 10.1038/ng.2714
|View full text |Cite
|
Sign up to set email alerts
|

A suppressor screen in Mecp2 mutant mice implicates cholesterol metabolism in Rett syndrome

Abstract: SummaryMutations in methyl CpG binding protein 2 (MECP2) cause Rett Syndrome, the most severe autism spectrum disorder. Re-expressing Mecp2 in symptomatic Mecp2 null mice dramatically improves function and longevity, providing hope that therapeutic intervention is possible in humans. To identify pathways in disease pathology for therapeutic intervention, a dominant ENU mutagenesis suppressor screen was carried out in Mecp2 null mice. Five suppressors that ameliorate symptoms of Mecp2 loss were isolated. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
224
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(252 citation statements)
references
References 64 publications
(76 reference statements)
24
224
3
1
Order By: Relevance
“…Mutations in specific nicotinic receptors can even cause a genetically transmissible form of epilepsy [27]. Moreover, decreases in cholinergic markers have been correlated with clinical severity in RTT patients [28,29]. The link between cholinergic systems and specific RTT phenotypes led us to hypothesize that dysfunction in cholinergic neurons might be involved in RTT.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in specific nicotinic receptors can even cause a genetically transmissible form of epilepsy [27]. Moreover, decreases in cholinergic markers have been correlated with clinical severity in RTT patients [28,29]. The link between cholinergic systems and specific RTT phenotypes led us to hypothesize that dysfunction in cholinergic neurons might be involved in RTT.…”
Section: Introductionmentioning
confidence: 99%
“…In an alternative approach involving mutagenesis screens in Mecp2-mutant mice, mutations in squalene epoxidase, the rate-limiting enzyme in cholesterol biosynthesis, were identified as suppressing RTT-associated phenotypes. Interestingly, cholesterol metabolism is altered and cholesterol levels are elevated in the brains of Mecp2 -/y male mice, all of which prompted the testing of statins with positive effects on some, but not all, categories of symptoms (14). Loss of function of MECP2 has also been associated with disruption of signaling through the AKT/mTOR pathway (15).…”
Section: Mecp2mentioning
confidence: 99%
“…One of the mitigating mutations introduced a premature stop codon in Sqle (squalene epoxidase), which encodes a key cholesterol biosynthesis enzyme. The authors showed that treatment of Mecp2 À/À mice with cholesterol-lowering statin drugs significantly improved motor function and lifespan, 73 suggesting that this widely used class of drugs may benefit individuals with Rett syndrome. A recently completed phase 2 clinical trial (NCT02563860) is evaluating this hypothesis, with results forthcoming (see Clinical Trials in Web Resources).…”
Section: Strategies To Identify Genetic Modifiers In Micementioning
confidence: 99%
“…A similar ENU-based mutagenesis screen identified modifier genes in the Mecp2 À/À (methyl CpG binding protein 2) mouse model of Rett syndrome (MIM: 312750). 73 As in humans,…”
Section: Strategies To Identify Genetic Modifiers In Micementioning
confidence: 99%